Feasibility study on the fabrication of eco-friendly construction material from glove former waste - Teh, Choo Chean (2024)
Rising global urbanization spurs demand for housing and infrastructure, driving up the need for construction like cement sand bricks. However, cement sand bricks are not highly environmentally friendly primarily due to a key component of these bricks which is cement. The manufacturing of cement involves the release of significant amounts of carbon dioxide into the atmosphere, contributing to greenhouse gas emissions and climate change. It is estimated that the cement industry accounts for 8% of the world’s carbon dioxide emissions. Next, the glove manufacturing industry generates glove former waste (GFW) which previously acted as ceramic mould in shaping and creating gloves. Vast amounts of GFW are being thrown into landfills since there is no way to recycle them. They can cause environmental problems such as groundwater pollution and soil pollution. GFW can be classified as a suitable pozzolana material since it has more than 70 % SiO2, Al2O3, and Fe2O3 based on its chemical composition. This research paper discusses the utilization of GFW as a substitute for cement in CSB production, aiming to mitigate environmental pollution in cement manufacturing and GFW management sectors. GFW was incorporated into cement sand brick as cement replacement with different replacement levels of 0%, 10 %, 15 %, 20 %, and 25 % respectively. The engineering properties and durability properties of all CSB specimens were assessed after 28 days of curing. According to the strength development of compressive strength, the GFW’s pozzolanic effect intensifies over time, particularly in later stages which promotes late strength development. The GFW-25 specimen exhibits the most optimal cement replacement percentage, satisfying standard requirements for compressive strength, flexural strength, bulk density, and water absorption rate. Besides, the fabrication of the GFW-25 specimen produces less carbon dioxide by 24.24 % and costs 19.85 % less compared to the conventional cement sand brick. This approach effectively creates a closed-loop system of circular economy by repurposing GFW to produce sustainable bricks, maximizing their value while simultaneously reducing the consumption of limited natural resources, such as cement. In addition, this research study is in line with SDGs 9, 11 and 13.